Performative body spaces : corporeal topographies in literature, theatre, dance, and the visual arts - Hallensleben, Markus (Critical studies (Amsterdam, Netherlands), 2010)
"The human body as cultural object always has and is a performing subject, which binds the political with the theatrical, shows the construction of ethnicity and technology, unveils private and public spaces, transgresses race and gender, and finally becomes a medium that overcomes the borders of art and life. Since there cannot be a universal definition of the human body due to its culturally performative role as a producer of interactive social spaces, this volume discusses body images from diverse cultural, historical, and disciplinary perspectives, such as art history, human kinetics and performance studies. The fourteen case studies reach from Asian to European studies, from 19th century French culture to 20th century German literature, from Polish Holocaust memoirs to contemporary dance performances, from Japanese avant-garde theatre to Makeover Reality TV shows. This volume is of interest for performance studies artists as well. By focusing on the intersection of body and space, all contributions aim to bridge the gap between art practices and theories of performativity. The innovative impulse of this approach lies in the belief that there is no distinction between performing, discussing, and theorizing the human body, and thus fosters a unique transdisciplinary and international collaboration around the theme performative body spaces."--Page 4 of cover